Ethical Leadership and Employee Mental Health: Comparing Private and Public Sector Employees - Haar, J; McGhee, P; Grant, P (ER Publishing Ltd, 2022)
Ethical leadership research mainly focuses on job outcomes while largely ignoring the potential influence on employee mental health. We seek to rectify this by examining the links between ethical leadership and work-life balance, anxiety, and depression. In addition, we include the role of organisational trust due to the important links between ethical leadership and trust. With two samples from the public sector and private sector, and using structural equation modelling, we find consistent effects across both samples. Ethical leadership is positively related to all outcomes, but organisational trust mediates the influence on work-life balance (fully in the public sector, and partially in the private sector), and fully mediates the influence towards anxiety and depression (both samples). In addition, we find that work-life balance also partially mediates the influence of organisational trust on anxiety and depression. This highlights the importance of organisational trust and work-life balance for ethical leaders to better alleviate mental health issues in the workplace.
Keywords: Ethical leadership; Organisational trust; Work-life balance; Mental health; Public sector; Private sector